2017
DOI: 10.3390/s17122841
|View full text |Cite
|
Sign up to set email alerts
|

Recent Enhancements to Interline and Electron Multiplying CCD Image Sensors

Abstract: This paper describes recent process modifications made to enhance the performance of interline and electron-multiplying charge-coupled-device (EMCCD) image sensors. By use of MeV ion implantation, quantum efficiency in the NIR region of the spectrum was increased by 2×, and image smear was reduced by 6 dB. By reducing the depth of the shallow photodiode (PD) implants, the photodiode-to-vertical-charge-coupled-device (VCCD) transfer gate voltage required for no-lag operation was reduced by 3 V, and the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Second, in the application, it is necessary to fit N (j) from the original image O (i, j) and then subtract it from O (i, j) to obtain I (i, j) representing the optical signal, which is calculated as follows. Accumulate (13) in the column direction as…”
Section: B Mathematical Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in the application, it is necessary to fit N (j) from the original image O (i, j) and then subtract it from O (i, j) to obtain I (i, j) representing the optical signal, which is calculated as follows. Accumulate (13) in the column direction as…”
Section: B Mathematical Theorymentioning
confidence: 99%
“…Some semiconductor processes and pixel structure designs that suppress the smear effect provide significant references for sensor development. Optimizations for P-N junctions can effectively reduce charge diffusion in the p-well below the photodiode [11], [12], [13], [14]. Moreover, double layer design and material replacement of the light shield can further avoid light penetration [7], [8], [15], [16].…”
mentioning
confidence: 99%
“…EMCCD ageing is a known factor that affects several device characteristics and manifests as a decrease in gain during the operational period. It has been hypothesised that this decrease in gain is due to holes becoming trapped beneath the DC gate electrode in the gain register [14] or attributed to damage to the gate dielectric by hot electrons during device operation [15]. Previous research has been primarily restricted to traditional EMCCDs and has demonstrated an approximately logarithmic decrease of gain with time [16].…”
Section: Emccd Ageingmentioning
confidence: 99%
“…This is relevant when considering EMCCDs device, which experience an additional damage process called ageing [10]. This process demonstrates as a decrease in the EM gain over the operating period of the device and has been attributed to charge trapping beneath the DC gate [11]. Traps are known to play a pivotal role in increasing the CTI, and there has been considerable interest in the nature of traps formed by radiation damage and subsequent effect on the charge transfer efficiency [12].…”
Section: Charge Transfer Efficiencymentioning
confidence: 99%